The Developing Countries and Electronic Filing: Case Burundi, Rwanda and the DRC - Eustache, Sirtaki (Archivist at the National Radio and Television of Burundi, 2016)
Archival heritage is essential to facilitate reforms and modernization in different areas of the state and society in Burundi, DRC and Rwanda and other countries also the archives of former colonial powers are often capitals including material heritage, proof, migration, borders, resource management or data for international research. It is important to respond to societal demands in the field; be it the academic sector, the associative fabric of civil society or state structures. Models in terms of good governance / facilitating access to archives may be proposed by some European countries. Countries like the DRC, Burundi and Rwanda are among the countries that are behind in terms of looking, access and archive management, mutual capacity building.